The human burst suppression electroencephalogram of deep hypothermia. Issue 10 (October 2015) - Brandon Westover, M.; Ching, ShiNung; Kumaraswamy, Vishakhadatta M.; Akeju, Oluwaseun; Pierce, Eric; Cash, Sydney S.; Kilbride, Ronan; Brown, Emery N.; Purdon, Patrick L.
Highlights We investigated the effects of deep hypothermia on the human electroencephalogram. Hypothermia induces a burst-suppression with bursts that are progressively longer and lower in amplitude, while the spectral content of bursts remains largely constant. These findings support a model in which burst suppression across diverse etiologies arises from widespread cyclical depletion of cerebral metabolic resources.